2017
DOI: 10.1148/radiol.2017151936
|View full text |Cite
|
Sign up to set email alerts
|

Does Reader Performance with Digital Breast Tomosynthesis Vary according to Experience with Two-dimensional Mammography?

Abstract: Purpose To assess whether individual reader performance with digital breast tomosynthesis (DBT) and two-dimensional (2D) mammography varies with number of years of experience or volume of 2D mammograms read. Materials and Methods After written informed consent was obtained, 8869 women (age range, 29-85 years; mean age, 56 years) were recruited into the TOMMY trial (A Comparison of Tomosynthesis with Digital Mammography in the UK National Health Service Breast Screening Program), an ethically approved, multicen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…Results from other studies indicate the need for training and workshops before reading DBT in screening [30, 31]. In our study, the radiologists’ experience in DM screen reading before the trial period varied from beginners to very experienced, the latter with more than 100,000 screen reads during their career as a breast radiologist.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Results from other studies indicate the need for training and workshops before reading DBT in screening [30, 31]. In our study, the radiologists’ experience in DM screen reading before the trial period varied from beginners to very experienced, the latter with more than 100,000 screen reads during their career as a breast radiologist.…”
Section: Discussionmentioning
confidence: 85%
“…A limitation of this study is the short time spent on training and workshops in DBT for radiographers before the start of the trial, which could have influenced the results in either direction [30, 31]. Moreover, we have not presented breast cancer detection data; this decision was based on per protocol power estimation, which showed that 2 years of screening—one screening round—was needed to show a 25–30% difference in the rate of screen-detected breast cancer between DBT and DM.…”
Section: Discussionmentioning
confidence: 99%
“…The TOMMY trial, carried out with 7060 patients in the United Kingdom, showed a marginal increase in sensitivity with borderline significance, with the addition of DBT to DM,45 while Tucker et al, using the same data concluded that sensitivity was increased for observers with less than 10 years of experience with the addition of DBT 46…”
Section: Results: Studies On the Optimal Use Of Digital Breast Tomosymentioning
confidence: 99%
“…Some studies show a significantly higher specificity with the addition of DBT to DM in screening 7,36,37,42,46,48,50,51. Other studies, however, concluded that there was a non-statistically significant increase 16,39,41.…”
Section: Results: Studies On the Optimal Use Of Digital Breast Tomosymentioning
confidence: 99%
“…This is true whether it is a radiologist requesting a second opinion when reading a digital breast tomosynthesis, a paediatrician leveraging a telemedicine platform to connect a patient with an allergist to select a more targeted food allergen panel, or a rheumatologist using a virtual reality platform to simulate the selection of lab tests and discuss results with a rheumatoid arthritis patient. The implementation of these solutions could raise the level of experience of physicians, which could lead to better outcomes [6,7,8,9]. …”
Section: Experiential Learning In Medicinementioning
confidence: 99%